Characteristics of occupational therapy and physiotherapy within the context of reablement in Swedish municipalities: A national survey. (25th December 2019) - Zingmark, Magnus; Evertsson, Bodil; Haak, Maria
Abstract: Reablement is a multidisciplinary, home‐based intervention implemented for people at risk of functional decline and losing independence aiming to optimise functioning and independence in activities of daily living. There is limited knowledge about what characterises the intervention and the role of different professionals. The purpose of this study was to explore the characteristics and differences of occupational therapy and physiotherapy interventions in terms of focus, content and duration within the context of reablement in Swedish municipalities. Web‐based surveys were used to collect data from 43 municipalities representing 25% of the population in Sweden. Data on intervention characteristics were reported for all cases receiving occupational therapy ( n  = 1, 395) and physiotherapy ( n  = 1, 006) over a 15‐week period. Data were presented descriptively, and differences between occupational therapy and physiotherapy were analysed using Chi‐square tests. The results indicated that reablement in Sweden was implemented for adults in all ages (19–103 years, median 81.0 years); 72% had home help. For both professions, a baseline assessment was made in fewer than half of all cases. There were significant differences between occupational therapists and physiotherapists regarding the focus and content as well as the number of contacts and duration of the intervention. For occupational therapists, walking indoors and self‐care were the largest focus areas, whereas for physiotherapists walking indoors and body function were the largest focus areas. For most cases, the intervention was completed within five sessions over a 6‐week period. This study provides the first picture of occupational therapy and physiotherapy within Swedish reablement contexts. In relation to the results, the focus of interventions, how assessments are made and how the intervention is implemented over time are issues that can be further elaborated.